PENGEMBANGAN ALAT CONTROL CHARGING PANEL SURYA MENGGUNAKAN ADUINO NANO UNTUK SEPEDA LISTRIK NIAGA - Prasetyo, Kurnifan Adhi; Yuniarti, Nurhening; Prianto, Eko (DPTE FT UNY, 2018)
Abstract The purpose of this research is to know the stages of manufacture, the performance and the development of solar panel control charging devices using arduino nano for commercial electric bicycle. Development of solar panel control charging device is expected to be used in utilizing solar thermal energy as a source of energy on a commercial electric bike with parameters generated from solar panels and battery charging. The result of this research is a solar panel charging control device that is used to control the input voltage from the solar panel to the battery used as a power source for the electric bicycle. The result are, the average battery charging power using 100 Watt Peak (WP) solar panel was 39.03 Watt with 160 minutes, the average efficiency of 85.82% and the yield of the battery voltage from 11 Vdc to 12.5 Vdc. While the average power charging battery using 300 WP solar panel is 57,43 Watt with time 50 minutes, average efficiency of 88.48% and battery voltage from 11 Vdc become 12,2 Vdc. Average percentage error of measurement parameter control charging solar panels below 10%. Keywords: control charging, solar panels, electric bike AbstrakTujuan dari penelitian ini adalah untuk mengetahui tahapan pembuatan, unjuk kerja dari pengembangan alat control charging panel surya menggunakan arduino nano untuk sepeda listrik niaga. Pengembangan alat control charging panel surya ini diharapkan dapat digunakan dalam memanfaatkan energi panas matahari sebagai sumber energi pada sepeda listrik niaga dengan parameter parameter yang dihasilkan dari panel surya dan pengisian aki. Hasil dari pembuatan proyek akhir ini berupa alat control charging panel surya yang digunakan untuk mengontrol tegangan masukan dari panel surya menuju aki yang dimanfaatkan sebagai sumber tenaga sepeda listrik niaga. Hasil pengujian, daya rata rata pengisian aki menggunakan panel surya 100 Watt Peak (WP) yang diuji adalah 39,03 Watt dengan waktu 160 menit, rata-rata efisiensi 85,82% dan hasil tegangan aki dari 11 Vdc menjadi 12,5 Vdc. Sedangkan daya rata rata pengisian aki menggunakan panel surya 300 WP yang diuji adalah 57,43 Watt dengan waktu 50 menit, rata-rata efisiensi 88.48% dan tegangan aki dari 11 Vdc menjadi 12,2 Vdc. Rata-rata persentase kesalahan parameter pengukuran alat control charging panel surya dibawah 10%. Kata Kunci : control charging, panel surya, Sepeda Listrik Niaga